2021
DOI: 10.2139/ssrn.3894375
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Neutralizing/SARS-CoV-2-S1-Binding Antibody Response With Adverse Effects and Immune Kinetics in BNT162b2-Vaccinated Individuals

Abstract: While mRNA vaccines against SARS-CoV-2 are exceedingly effective in preventing symptomatic infection, their immune response features remain to be clari ed. In the present prospective study, 225 healthy individuals in Japan, who received two BNT162b2 doses, were enrolled. Correlates of BNT162b2-elicited SARS-CoV-2-neutralizing activity (50% neutralization titer: NT 50 ; assessed using infectious virions) with various determinants were examined and the potency of serums against variants of concerns was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Additionally, in 56% of participants, vnAb titers remained above 200 IU/mL, representing an estimated 75% protection against infection from SARS-CoV-2 Wuhan (Figure 3). Consistent with previous reports, 17,27,28 we observed a negative correlation between vnAb titers and age (Figure 6). Older participants on average were less likely to maintain titers above 200 IU/mL and demonstrated more rapid rates of vnAb decay.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, in 56% of participants, vnAb titers remained above 200 IU/mL, representing an estimated 75% protection against infection from SARS-CoV-2 Wuhan (Figure 3). Consistent with previous reports, 17,27,28 we observed a negative correlation between vnAb titers and age (Figure 6). Older participants on average were less likely to maintain titers above 200 IU/mL and demonstrated more rapid rates of vnAb decay.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have reported that SARS-CoV-2 vnAb titers in convalescent individuals [13][14][15] and vaccinees 16,17 show rapid early decay that slows over time. This trend is consistent with a burst of short-lived antibody secreting cells producing peak vnAb titers, which decay rapidly until reaching a slowly declining plateau maintained for months to years by long-lived memory B cells.…”
Section: Longitudinal Dynamics Of Vnabs Following Vaccinationmentioning
confidence: 99%
“…The NAb in serum was determined by quantifying the serum-mediated suppression of the cytopathic effect (CPE) of each SARS-CoV-2 strain in VeroE6 TMPRSS2 cells [10, 11]. The obtained routes of the cells and each virus are described in Supplemental Text 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The diluted sera were incubated with 50% tissue culture infectious dose (TCID 50 ) of the virus at 37°C for 20 minutes (final serum dilution range of 1:40 to 1:25000), after which the serum-virus mixtures were inoculated with VeroE6 TMPRSS2 cells (1.0×10 4 /well) in 96-well plates. The SARS-CoV-2 strains used in these assays are as follows: a Wuhan, wild-type strain (SARS-CoV-2 05-2N ) [12], a Delta variant (SARS-CoV-2 TKYTK1734/2021 ), and an Omicron BA.1 variant (SARS-CoV-2 TKYX00012/2021 ). After culturing the cells for 3 to 5 days, the levels of CPE observed in SARS-CoV-2-exposed cells were determined using the WST-8 assay using the Cell Counting Kit-8 (Dojindo, Kumamoto, Japan).…”
Section: Neutralizing Antibody Testingmentioning
confidence: 99%
“…BNT162b2, an mRNA-based SARS-CoV-2 vaccine (Pfizer-BioNTech), is one of the most effective COVID-19 vaccines (10) and has been approved by more than 130 countries worldwide. However, several studies have reported that the COVID-19 vaccine shows high interpersonal variability in terms of humoral and cellular responses, such as those with respect to anti-SARS-CoV-2 spike immunoglobulin (Ig)G (11-17), IgA (15, 16), IgM (16), neutralizing antibodies (18-20), and CD4 + & CD8 + T cells (18, 19, 21). The long-term sustainability of SARS-CoV-2 neutralizing antibodies is crucial for the protection against infection and hospitalization.…”
Section: Introductionmentioning
confidence: 99%